STRATEGI PENGELOLAAN PEMBELAJARAN BERBASIS DISKUSI DALAM MEMOTIVASI BELAJAR SISWA - Intan Mifthaul Jannah; Devi Wahyu Ertanti; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This study aims to identify problems related to student motivation in online learning through learning management strategies by applying the discussion method. This study uses qualitative research to collect data information with observation and interview techniques and complete with documentation. The problem found by researchers in the fourth grade of SD Islam Bani Hasyim is the decline in students' learning motivation due to the lack of interaction between teachers and students and also students are getting bored with online learning. To overcome this problem, the researcher uses this discussion-based learning management strategy in order to increase students' learning motivation because with discussion learning there will be interaction between teachers and students because this will increase or increase student learning motivation